Konsep Akhlak Bagi Peserta Didik dalam Pendidikan Agama Islam Menurut Ibnu Al-Qayyim Al-Jauziyyah - Ananda Octavianie Fadilla; Ajat Rukajat; Khalid Ramdhani (AS-SABIQUN, 2022)
Various phenomena related to the lack of morals and morals among students are currently a decline in the cultural changes brought by the western world to the Muslim community, especially among students, therefore researchers will examine a discussion related to research on the work of bnu Qayyim Al- Jauziyah who is one of the previous scholars who focused on studies and discussions in the field of morality. On the basis of scientific studies. The purpose of this study was to find out the scope of the concept of morality for students in the aspect of the study of Islamic Religious Education which was taken from the author of Ibn Al-Qayyim Al-Jauziyyah by using exemplary and habituation methods so that the formation of good morals for students. The method used in this research is the writer takes the library research method using a qualitative approach taken from various theories and experts in their fields with literary data collection techniques. The results in this study discuss the moral concept of students in the review of Islamic Religious Education and the opinion of the Islamic scholar of moral science Ibn Al-Qayyim Al-Jauziyyah who discusses the good and bad behavior of a person in aspects of his life by getting used to the cultivation of good moral behavior to students which has been carried out since their age is still small by applying the way of example and habituation. The role of both parents, and support from the environmental community and school will determine the results of the formation of good and bad behavior in the morals of students.